Recent Findings in Malaria Emergence of Piperaquine-Resistant Plasmodium falciparum Genes in Malaria Endemic Areas of Indonesia: a Literature Review - Ayu Nurdiantika Sari; Tri Yunis Miko Wahyono; Ayleen Alicia Kosasih; Yoshida Aussiana Samosir; Rania Rifdah Taufiq; Inge Sutanto (Master of Epidemiology, School of Postgraduate Studies, Diponegoro University, Indonesia, 2023)
Background: In recent years, artemisinin and piperaquine (PPQ) resistance in the Greater Mekong Sub-region alarmed Southeast Asian countries, especially those relying on artemisinin- based combinations as antimalarial drugs. This study aims to review the current status of malaria research and examine the frequencies of piperaquine resistance in Plasmodium falciparum isolates originating from malaria-endemic areas in Indonesia.Methods: We undertook a review to identify empirical data on antimalarial piperaquine-inclusive artemisinin combination therapies (ACT) in Indonesia using studies conducted since 2015. Journal articles were searched using the keywords combination of malaria, piperaquine, Pfcrt, Pfmdr, Pfpm2, and Indonesia. The search was conducted in four databases. Trends in empirical data were summarised in a table and compared with emerging malaria prevalence and conditions in Indonesia.Results: Our study found that dihydroartemisinin-piperaquine (DHA-PPQ) is still effective in most area. Survey of PPQ resistance in regions using DHA-PPQ as the first-line treatment heavily depends on phenotypic tests of the given drug resistance. Molecular surveys exploring polymorphisms of Pfcrt, Pfmdr1, and Pfpm2 were not found.Conclusion: This study supports the use of dihydroartemisinin-piperaquine as the first-line antimalarial drug in malaria endemic areas of Indonesia. Further research examining efficacy is required to monitor piperaquine resistance in Indonesia.